1283. New Generation Antiviral Conjugate (AVC): Stable, Safe, and Single. (31st December 2020) - Ong, Voon; Levin, James; Borchardt, Allen; Brady, Thomas P; Lam, Thanh; Noncovich, Alain; Fortier, Joanne; Amundson, Karin; Locke, Jeffrey B; Almaguer, Amanda; Dedeic, Nicholas; Hough, Grayson; et al.
Abstract: Background: CD377 is a novel antiviral Fc-conjugate (AVC) development candidate for influenza prevention and treatment, comprising multiple copies of a novel potent small-molecule antiviral and the Fc domain of human IgG1. CD377 was designed as a stable, long-acting molecule for treatment and prevention of influenza A and B. Studies were conducted to characterize CD377 stability/pharmacokinetics (PK), single-dose efficacy in influenza models, and safety/toxicology. Methods: PK in the mouse (1-100 mg/kg), rat (5-50 mg/kg), ferret (3 mg/kg), and monkey (5-20 mg/kg) were studied by sampling plasma over a 1-2 week interval. Plasma levels of intact molecule and total Fc were measured by neuraminidase (NA)-capture and Fc-capture with Fc-detection ELISA, respectively. Two-week safety/toxicology (bodyweight, coagulation, clinical signs, chemistries, hematology, cytokines, urinalsis, histopathology) was evaluated in monkeys (5-20 mg/kg on days 1 and 8). Prophylaxis efficacy was studied in a lethal influenza mouse model using a single dose of CD377 (0.3–3 mg/kg) 28 days prior to intranasal (IN) challenge with 3x the LD95 of A/California/07/2009 (H1N1)pdm, A/Hong Kong/1/68 (H3N2), or B/Malaysia (Victoria lineage). Treatment efficacy was studied in a similar mouse model using a single dose of CD377 (0.3–3 mg/kg) administered 2 hours after IN challenge with A/CA/12/2012 (H1N1)pdm. Results: Plasma concentrations measured by Fc-capture/Fc-detection and NA-capture/Fc-detection were comparable, indicating that CD377 remained intact in vivo. In species tested, CD377 t1/2 was 3–10 days. Dose proportional increases in exposure were observed, notably from 1–100 mg/kg in mouse. High bioavailability (77%) was observed after subcutaneous (SC) or intramuscular (IM) administration. A single SC dose of 1 mg/kg administered 28 days prior to infection provided 100% protection against H1N1, B, and H3N2 subtypes in mouse (Fig. 1). Treatment efficacy was observed with a single 0.3 mg/kg IM dose. The 2-week monkey toxicology study showed no adverse effects. Figure 1. Efficacy (Survival and Body Weight) of CD377 in a 28-Day Prevention Model Against Influenza H1N1, H3N2, and B Subtypes in Mouse (IN infection challenge on Day t=0 and CD377 dosed t–28 days). Conclusion: The stability and safety of CD377, together with its long half-life and efficacy with a single dose, support the potential of CD377 as a long-acting, novel AVC for the prevention and treatment of influenza. Disclosures: Voon Ong, PhD, Cidara Therapeutics, Inc. (Employee, Shareholder) James Levin, PhD, Cidara Therapeutics (Shareholder) Allen Borchardt, PhD, Cidara Therapeutics (Employee) Thomas P. Brady, PhD Chemistry, Cidara Therapeutics (Employee) Thanh Lam, PhD, Cidara Therapeutics (Shareholder) Alain Noncovich, PhD, Cidara Therapeutics (Shareholder) Joanne Fortier, BSc, Cidara Therapeutics (Employee, Shareholder) Karin Amundson, B.S., Cidara Therapeutics (Shareholder) Jeffrey B. Locke, PhD, Cidara Therapeutics, Inc. (Employee, Shareholder) Amanda Almaguer, Bachelors, Cidara Therapeutics, Inc. (Employee, Shareholder) Nicholas Dedeic, n/a, Cidara Therapeutics (Employee) Grayson Hough, MS - Chemistry, Cidara Therapeutics (Employee) Jason Cole, PhD, Cidara Therapeutics (Shareholder) Simon Döhrmann, PhD, Cidara Therapeutics (Shareholder) Rajvir Grewal, n/a, Cidara Therapeutics, Inc. (Employee, Shareholder) Elizabeth Abelovski, B.S., Cidara Therapeutics (Shareholder) James M. Balkovec, PhD, Cidara Therapeutics (Consultant, Shareholder) Ken Bartizal, PhD, Cidara Therapeutics, Inc. (Consultant, Shareholder) Les Tari, PhD, Cidara Therapeutics (Shareholder)